Грамоти Бобрицького воєводи Кирила Ушакова 1649 року (з історії заснування острогу Кам’яне) - Осадчий, Є.М. (Сіверщина в історії України, 2020)
До наукового обігу вводяться тексти двох грамот, присвячених розвідкам воєводи з містечка Бобрик території навколо городища Кам’яне. Невелике прикордонне містечко знаходилося у низинній місцевості і постійно піддавалося нападам татар. Відразу
після введення нового гарнізону до Бобрика постало питання про
будівництво нової фортеці, яка б могла стати опорним пунктом
на кордоні з Річчю Посполитою. Для цих потреб підходило Кам’яне городище, що знаходилося на високому мисі із стрімкими схилами. Його розташування дозволяло контролювати значну територію кордону між Річчю Посполитою та Московським царством,
а також ділянку Сагайдачного шляху. The publication is dedicated to the introduction into the scientific
circulation of two letters of the governor of the city of Bobryk Kyryl
Ushakov dated 1647. This year, the Polish-Lithuanian Commonwealth
transferred several border towns to the Moscow kingdom. The city of
Bobryk was located in lowland and did not have significant fortifications.
From the moment the Moscow garrison appeared in it, the raids of the
Tatars became more frequent. To strengthen the defense of the border,
it was necessary to find a suitable place for the foundation of a new
fortress. For this governor, Kyryl Ushakov equipped an expedition to the
Kamiane hillfort in order to find out its defense potential. At the end of
the expedition, two reports were compiled in the name of Tsar Oleksii
Mykhailovych. In the first, the voivode informs that the expedition to
the hillfort took place. The second document is an extended report with
the characteristics of the hillfort and a description of the area in which
it is located. The document is dated December 9, 1647. The letters are
written in cursive, typical of the middle of the XVII century. Documents
have text damage and loss associated with storage conditions.